The Role Of Social Media On Tax Awareness Income In Micro Small To Medium Enterprises (SME’s) In Surabaya - Susilo, Agus (Jurnal Ekonomi, 2024)
The general public's understanding of taxation is critical. Taxation is one of the most important sources of state revenue for infrastructure development and social welfare. There are numerous reasons why citizens refuse to pay their taxes. Educating people on the need for paying taxes can help. This study takes the problem formulation, namely, what is the role of social media in optimizing awareness of paying taxes for Small to Medium Enterprises (SME's) or MSMEs, and while the goal is to discover what the role of education is in educating about optimizing awareness of paying taxes and knowing how social media plays a role in educating taxation for MSMEs to increase tax awareness. It is believed that this research would provide educational understanding. A qualitative technique is used in this investigation. Secondary data was obtained through interviews and direct observation of MSMEs, as well as indirect and literature studies through books, journals, DJP websites, and various other sources. Because the number of social media users increases year after year, tax education is performed through social media. As a result, if it is supported in the future, it will be quite effective. This will have a significant impact on the increase in tax awareness among MSMEs.